The Effectiveness of Reciprocal Teaching in Enhancing Reading Comprehension in Majalengka - Ginanjar, Teten; Nurhidayat, Eka; Dwika Herdiawan, Rama (Papanda Publisher, 2024)
This study investigates the effectiveness of Reciprocal Teaching (RT) in improving reading comprehension among vocational high school students in Majalengka, Indonesia. Grounded in Vygotsky’s Zone of Proximal Development (ZPD), RT employs four metacognitive strategies—predicting, questioning, clarifying, and summarizing—within collaborative learning structures. A quasi-experimental design was used involving 64 students divided into experimental and control groups. Pre- and post-tests were conducted to assess comprehension improvements. The experimental group, taught using RT, showed a statistically significant increase in scores compared to the control group, confirming RT's efficacy in enhancing comprehension skills. Findings support RT’s potential for broader adoption in Indonesian EFL classrooms to foster metacognitive awareness and independent learning.